Musholla Building Planning Assistance at SMA Negeri 26 Batam - Ade Jaya Saputra; Bennedict Christopher Huang; Rafi Samudra Indrawan; Kurnia Gilang Ramadhani; Rizska Dwi Kartika; Malvin Iuryanto (Universitas Internasional Batam, 2024)
A building is an infrastructure with several structural and architectural components erected to help all human activities. Mosques and mushollas are buildings that become unique places of worship for Muslims. The existence of Musholla has grown as a necessity for many infrastructures, including factories, offices, and schools or madrasas. Public facilities such as mosques and mushollas require calculations in terms of sound design because of the broad land. An expert with experience making building designs is needed to get the design as expected. This is the main requirement of what is expected by SMAN 26 Batam. The school plans to build a mosque or musholla because it does not have a place yet to worship and do other religious activities for the Muslim community inside the school. The purpose of this community service is to assist in the planning process of the musholla construction, where the project is expected to benefit the school community later. The output of this activity is the submission of 2D and 3D designs and drawings, calculation of a Budget Estimate Plan (BEP), and construction implementation project schedule (Banana Curve).